THE EFFECTIVENESS OF ANIMATION VIDEO TECHNOLOGY IN ARABIC LANGUAGE TEACHING ON STUDENTS OF ISLAMIC ELEMENTARY SCHOOL OF METRO CITY - Akla, Akla (AKADEMIKA: Jurnal Pemikiran Islam, 2021)
Students' difficulties in learning come from boredom, lack of excitement, and laziness stimulated by monotonous and uninteresting learning. This research aims to analyze three things: (1) how the use of animation video technology takes place in the process of Arabic learning; (2) how the students' learning attitude performs while using animation video technology; and (3) how the effectiveness of the use of animation video technology enhances the students' Arabic language mastery. This research method uses mixed-method research by combining qualitative and quantitative methods, focusing on the data collection and data analysis process. This research's respondents are the students of State Islamic Elementary School of Metro City, Lampung totalling 70 students. The research instrument is the list of questions to gain data on the implementation of learning using the animation video technology. The test instrument to get data about the results of Arabic learning before and after using animation video technology. This study results in findings that animation video technology has created a psychological atmosphere that is fun for the children. The feeling of pleasure has developed students' positive attitude in learning. The results of the t-test show that sig (2-tailed) is equal to 0.019 < the value of α (0.05), which means that there is a significant influence on the use of animation video technology on students' Arabic langauge ability. This study concludes that animation video technology designed interestingly has overcome various difficulties of students' learning. This study recommends using animation video technology in teaching the Arabic language.